Estimasi Penurunan Berat Kapal dengan Aplikasi Struktur Sandwich pada Double Hull Tanker 5704 DWT - Heni Siswanti; Siti Ahdiatun Nurzanuba; M. Musta'in (POLITEKNIK NEGERI BENGKALIS, 2023)
Double hulls on tankers are a must to protect the environment from the oil spill effects of ship leakage. However, a double hull structure produces a heavy structure, reducing the payload. For decades, designers have tried reducing the structure's weight by applying lightweight material such as polyurethane-steel sandwich. Strong steel faceplates with a low-density polyurethane core promise significant weight reduction. Nevertheless, structural strength remains a major consideration in the design of sandwich structures. This study evaluates the structural weight reduction of replacing a conventional stiffened plate structure with a sandwich structure on a double hull tanker 5704 DWT. It also analyzes the structural strength using the finite element method. The results show that applying a sandwich structure on a double-hull tanker significantly reduced the structure's weight without decreasing structural strength. It is proven that the application of sandwich structure potentially increases ship payload.